The Influence of Work Environment and Compensation on Employee Performance at PT. Hadji Kalla Toyota Palopo - Nisa, Nisa; Sukri, Sukri; Riyanti, Riyanti (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to analyze whether the work environment and compensation influence employee performance at PT. Hadji Kalla Toyota Palopo, using a quantitative approach as the research method. The population in this study includes all 70 employees, while the sample consists of 41 employees, determined using Slovin's formula. Data collection was conducted through questionnaires. Data analysis was performed using SPSS. The findings of this study indicate that the work environment has a positive and significant effect on employee performance, compensation does not show an influence on employee performance, and simultaneously, the work environment and compensation have a positive and significant effect on employee performance at PT. Hadji Kalla Toyota Palopo. The implications of these findings suggest that the company should pay attention to and improve the work environment and provide appropriate and fair compensation to employees to enhance their performance, thereby achieving the company's objectives.